A map of evidence using transcranial direct current stimulation (tDCS) to improve cognition in adults with traumatic brain injury (TBI) - Schwertfeger, Julie Lynn; Beyer, Charlotte; Hung, Paul; Ung, Nathaniel; Madigan, Caroline; Cortes, Alvi Renzyl; Swaminathan, Bharathi; Madhavan, Sangeetha (Frontiers in Neuroergonomics, 2023)
Cognition impairments often occur after traumatic brain injury and occur at higher rates in military members. Cognitive symptoms impair daily function, including balance and life quality, years after TBI. Current treatments to regain cognitive function after TBI, including medications and cognitive rehabilitation, have limited effectiveness. Transcranial direct current stimulation (tDCS) is a low-cost non-invasive brain stimulation intervention that improves cognitive function in healthy adults and people with neuropsychologic diagnoses beyond current interventions. Despite evidence for tDCS to improve cognition generally, only two small TBI trials are in the most recent systematic review of tDCS effectiveness for cognition following neurological impairment and there are no TBI tDCS trials for balance. Methods: A scoping review using a peer reviewed search of eight databases was completed in July 2022. Two assessors completed a multi-step review and completed data extraction on included studies using a priori items recommended in tDCS and TBI research guidelines. Results: The 399 results were reviewed for inclusion and 12 met criteria and had data extracted by two assessors using Google forms. Consensus on combined data results included a third assessor when needed. No studies using tDCS for cognition related balance were found. Discussion: Guidelines and technology measures increase identification of brain differences that alter tDCS effects on cognition. People with mild-severe and acute-chronic TBI tolerated and benefited from tDCS. TBI-related cognition is understudied, and systematic research that incorporates recommended data elements are needed to advance tDCS interventions to improve cognition after TBI weeks to years after injury.